2018
DOI: 10.18203/2320-1770.ijrcog20184493
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency in pregnancy and its effects on neonatal outcome

Abstract: Background: India has one of the highest Vitamin D deficiency rates in pregnancy in the world and yet we have limited research to study its various effects from our country. We aim to study the prevalence of Vitamin D deficiency in pregnancy and effect on neonatal outcome after supplementation.Methods: 200 pregnant women were recruited at 26 weeks and more. They were divided into sufficient group (normal levels of the vitamin), supplemented group (recruited at 26 weeks and supplemented for 8 weeks) and unsuppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…14 In a study by Gupta S, et al, out of the total 137 women with VDD (less than 20ng/ml), 31.4% were multigravida and 68.6% were primigravida, out of the total 24 women with severe VDD (less than 4ng/ml), 20.8% were multigravida and 79.2% were primigravida and out of the total 28 women with Vitamin-D insufficiency (between 20-30ng/ml), 32.1% were multigravida and 67.9% were primigravida. 15 In this study of mine, among the 21 cases with VDD 52.38% of them were working and 47.61% were nonworking; 14.28% were vegetarian and 85.71% of them were non-vegetarian; only 1 of them had history of intake of vitamin-D and calcium intake; 76.19% had sun exposure of less than 1 hr daily and 23.80% of them had sun exposure more than 1 hour daily. The exposure duration was 60 minutes; 47.80% of the subjects had less than an hour of sun exposure during the day while 52.20% had more than 60 minutes.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…14 In a study by Gupta S, et al, out of the total 137 women with VDD (less than 20ng/ml), 31.4% were multigravida and 68.6% were primigravida, out of the total 24 women with severe VDD (less than 4ng/ml), 20.8% were multigravida and 79.2% were primigravida and out of the total 28 women with Vitamin-D insufficiency (between 20-30ng/ml), 32.1% were multigravida and 67.9% were primigravida. 15 In this study of mine, among the 21 cases with VDD 52.38% of them were working and 47.61% were nonworking; 14.28% were vegetarian and 85.71% of them were non-vegetarian; only 1 of them had history of intake of vitamin-D and calcium intake; 76.19% had sun exposure of less than 1 hr daily and 23.80% of them had sun exposure more than 1 hour daily. The exposure duration was 60 minutes; 47.80% of the subjects had less than an hour of sun exposure during the day while 52.20% had more than 60 minutes.…”
Section: Discussionmentioning
confidence: 71%
“…14 Contradictory to this study in a study by Gupta S, et al out of the total 137 women with VDD (less than 20ng/ml), 26 (19.0%) were non-vegetarian and 111 (81.0%) were vegetarian, out of the total 24 women with severe VDD (less than 4ng/ml), 5 (20.8%) were non-vegetarian and 19 (79.2%) were non-vegetarian and out of the total 28 women with Vitamin-D insufficiency (between 20-30 ng/ml), 4 (14.3%) were non-vegetarian and 24 (85.7%) were vegetarian. 15 Regarding the Vitamin-D level in pregnant women in this study where the Vitamin-D level was categorized according to IOM; VDD, Vitamin-D insufficiency and sufficient was seen in 44.68%, 31.91%, and 23.40% pregnant women respectively. A study by Shrestha D, et al in Bhaktapur revealed that the prevalence VDD (<20ng/ml) and insufficient Vitamin-D level (20-30 ng/ml) among pregnant women at the time of delivery were 81% (64/79) and 11.39% (9/79) respectively.…”
Section: Discussionmentioning
confidence: 76%